Media Reality of Modern Education: Historiography of the Problem of Media Literacy and Media Competence - Loboda, Svitlana (Journal of Vasyl Stefanyk Precarpathian National University, 2023)
The modern educational paradigm exists in media reality. Accordingly, the challenges and trends of the modern educational space are formed around the problem of media literacy and media competence. The aim of the study is to analyze the best educational practices of the United States, Canada and the United Kingdom in the sphere of media literacy and media competence in order to identify the innovative potential of modern reforms, understand and realize modern processes in education, and design its future. The research is based on the analysis of contemporary scientific and pedagogical discourse around the issue of media literacy and media competence. The study of this issue is based on a comprehensive retrospective analysis of the works of scholars from the United States, as well as Canada, the United Kingdom. The author analyzes the historiography of this issue, which reflects different stages of its development, using a complex of historiographical and historical-comparative methods and approaches. The results of the study made it possible to identify and describe the content, focus, specificity and factors of the development of the problem of media literacy and media competence as key components of the transformation processes of the modern educational paradigm and determine the value-content orientations of scientific and pedagogical discourse. Based on the results of the analysis of the historiography of the problem, it is concluded that the theoretical basis of the problem of media literacy and media competence is made up of pedagogical, sociological, psychological and philosophical theories; the impact of media on the formation of the individual in particular and the community in general; research on information and information-psychological security of the individual; provisions on the influence of the mass media on the formation of personal qualities and behavior; provisions on the impact of informatization on the learning process; research on psychological protection of the individual in the information environment; research on the phenomenon of information culture; concepts of personal information culture development; general scientific provisions of the theory and history of the periodical press and its influence on the formation of consciousness; a provision on the need to enrich pedagogical experience by combining the best examples of pedagogical theory and practice from different countries in order to preserve universal values, ideals and individual rights.